The synthesis of theory and practice in heritage studies - a way toward prosperity (Case study from Croatian ex-war area) - Babić, Darko muzeolog (2008)
After the war, in 1995, the revitalisation started but progressed slowly. During 2004 multidisciplinary group of experts initiated a heritage based project within the area. The core idea of the project is that the local, common heritage could be the main catalyst of the future regional development.
Projekt MZOS
ENG